Mobile Learning Berbasis Android Sebagai Media Pembelajaran Pendidikan Agama Islam - Sofia Zaini Kulbi (Nazhruna: Jurnal Pendidikan Islam, 2019)
Advances in communication technology affect all aspects including aspects of education. An educator is required to create active, effective and fun teaching and learning activities. Related to this, the learning of Islamic Religious Education (PAI) is generally still monotonous in using learning media so that students feel bored in learning PAI. PAI’s teacher at SMK Wahana Karya tries to make an innovation in Islamic Education learning, namely by using Android-based mobile learning. This is based on the background of students who on average already use Android in everyday life. So, this study describes android-based mobile learning as a learning medium for Islamic religious education at SMK Wahana Karya. This research uses qualitative methods, where the researcher makes direct observations and interviews. Sources of data used are from school archives, school websites, interviews with principals, Islamic education teachers, and students of SMK Wahana Karya. The results of this study are, although there are still some obstacles, namely in terms of signal and classroom atmosphere conditioning. However, apart from that the use of mobile learning is considered effective and attracts students in learning Islamic Education.